Corporate Social Responsibility Optimization as Collaborative Funding Innovation to Support Sustainable Development - Lindawati Lindawati; Yudhanty Parama Sany; Sak Khie; Iwan Syahrul Anwar; Dewi Listiorini (Jurnal Ekonomi dan Studi Pembangunan, 2024)
During the pandemic, development progress is hindered by budget constraints. Meanwhile, the business sector's contribution to development is minimal and charitable, with no significant impact. To address this issue, a program called "Kembang Jawara" has been introduced to optimise Corporate Social Responsibility (CSR) funding for development programs. This study aimed to explore the funding innovation called "Kembang Jawara" through a case study. The primary data was gathered through focused group discussions and interviews with the Regional Development Planning, Research and Development Agency of Subang Regency. The secondary data was sourced from proposals, work plans, reports, and policies related to Kembang Jawara. The analysis was conducted in four stages: data collection, data reduction, data presentation and visualisation, and conclusion drawing. The program involves compiling an inventory of development programs, coordinating with regional apparatus and the provincial government, socialising with potential CSR partners, and hosting a CSR Awards ceremony. In 2020, 13 companies contributed Rp4.930 billion to the program; in 2021, this increased to 15 companies, contributing a total of Rp8.565 billion. This innovative initiative is in line with SDG 17 and has the potential to be replicated by other local governments. However, areas of improvement include enhancing communication with the business sector, providing detailed information on development programs and CSR schemes, and recording program activities through a website-based application.